Psycho-demographic factors predisposing school adjustment among In-school adolescents in Osun state, Nigeria. - Ernest Okpako (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
The study examines the Psycho-demographic factors predisposing school adjustment among In-school adolescents in Osun state, Nigeria. The study adopted a descriptive design of correlational type. A Sample of three hundred In-school adolescents were selected using a multi-stage sampling technique. Data collected were analyzed using Pearson Product Moment Correlation, T-test and Multiple regression analysis. Results indicated School adjustment positively correlated with peer pressure (r= .461, p< 0.05), emotional instability (r = .665, p<0.05) while school adjustment is negatively correlated with gender (r= -.332, p<0.05). All the independent variables jointly accounted for 48.5% variance in predicting school adjustment among In-school adolescents. Two out of three predictors (emotional stability and gender) are potent predictors of school adjustment. The most potent factor was emotional stability (β = .591, t= 11.611, P<0.05), followed by gender (β = -.205, t= -4.757, P<0.05 except peer pressure (β = .062, t= 1.198, P>0.05) which is not a potent predictor of school adjustment. This implies that, an increased influence of emotional stability will increase school adjustment by 59.1% and gender will increase school adjustment by 20.5%. Also, the T-test analysis reveal a significant difference in the school adjustment of male and female; t (298) = 6.081, p<0.05.